2016
DOI: 10.1186/s12993-016-0090-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of parsley (Petroselinum crispum, Apiaceae) juice against cadmium neurotoxicity in albino mice (Mus Musculus)

Abstract: Background Parsley was employed as an experimental probe to prevent the behavioral, biochemical and morphological changes in the brain tissue of the albino mice following chronic cadmium (Cd) administration.Methods Non-anesthetized adult male mice were given parsley juice (Petroselinum crispum, Apiaceae) daily by gastric intubation at doses of 10 and 20 g/kg/day. The animals were divided into six groups: Group A, mice were exposed to saline; Groups B and C, were given low and high doses of parsley juice, respe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 56 publications
1
32
1
Order By: Relevance
“…In the motor cortex, cellular densities of astrocytes and neurons were decreased after inorganic mercury exposure ( Figures 8 , 9 ). Previous toxicological studies already indicate that the decrease in the number of both astrocytes and neurons is usually associated with functional damage observed in behavioral tests ( Akagi and Nishimura, 1991 ; Suzuki et al, 2004 ; Flores-Montoya et al, 2015 ; Maodaa et al, 2016 ). In addition, in vitro exposure to inorganic mercury causes cell death in human neurons and astrocytes ( Lohren et al, 2015 ).…”
Section: Discussionmentioning
confidence: 96%
“…In the motor cortex, cellular densities of astrocytes and neurons were decreased after inorganic mercury exposure ( Figures 8 , 9 ). Previous toxicological studies already indicate that the decrease in the number of both astrocytes and neurons is usually associated with functional damage observed in behavioral tests ( Akagi and Nishimura, 1991 ; Suzuki et al, 2004 ; Flores-Montoya et al, 2015 ; Maodaa et al, 2016 ). In addition, in vitro exposure to inorganic mercury causes cell death in human neurons and astrocytes ( Lohren et al, 2015 ).…”
Section: Discussionmentioning
confidence: 96%
“…In modern medicine, parsley has been exhibited antioxidant, immunosuppressant, cytoprotective, diuretic, antibacterial and antifungal activities [73]. It is one of the most used medicinal plants to treat renal diseases [74], antihyperlipidemic, antihyperglycemic [75], and anti-microbial [76] [77] [78]. Parsley has been used as antiurolithiasis, antiseptic of the urinary tract, diuretic, anti-dote, and anti-inflammatory in folklore and traditional medicines [73].…”
Section: Parsley (Petroselinum Crispum)mentioning
confidence: 99%
“…Tea, a potent antioxidant with metal chelating properties owing to its numerous hydroxyl groups [38,39] has been shown to have neuroprotective effects in a number of neuropathological conditions linked to excitotoxicity and oxidative stress [40]. A few studies have reported significant beneficial effects of plant extracts including tea against metal-induced neurotoxicity [19,41,42,43,44]. However, to the best of our knowledge, this is the first study to compare the protective effects of polyphenol rich tea (Camellia sinensis) and EDTA against Cdinduced neurotoxicity.…”
Section: Discussionmentioning
confidence: 99%